2019
DOI: 10.1377/hlthaff.2019.00918
|View full text |Cite
|
Sign up to set email alerts
|

Access, Quality, And Financial Performance Of Rural Hospitals Following Health System Affiliation

Abstract: More than a hundred rural hospitals have closed since 2010. Some rural hospitals have affiliated with health systems to improve their financial performance and potentially avoid closure, but the effects of affiliation on rural hospitals and their patients are unclear. To examine the relationship between affiliation and performance, we compared rural hospitals that affiliated with a health system in the period 2008-17 and a propensity score weighted set of nonaffiliating rural hospitals on twelve measures of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 26 publications
(24 reference statements)
2
54
1
Order By: Relevance
“…A recent study that evaluated rural hospital affiliations advanced our understanding of changes in certain services associated with affiliations 53 . Those services included outpatient nonemergency visits, on‐site diagnostic imaging technologies, and the availability of obstetric and primary care services 53 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study that evaluated rural hospital affiliations advanced our understanding of changes in certain services associated with affiliations 53 . Those services included outpatient nonemergency visits, on‐site diagnostic imaging technologies, and the availability of obstetric and primary care services 53 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study that evaluated rural hospital affiliations advanced our understanding of changes in certain services associated with affiliations 53 . Those services included outpatient nonemergency visits, on‐site diagnostic imaging technologies, and the availability of obstetric and primary care services 53 . The authors stated that, for affiliated hospitals, they “found no evidence that rural hospitals were reducing inpatient services overall and shifting more services to outpatient settings.” 53 That study differed from our study in several ways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But a new study indicates that, although affiliation improved rural hospitals' finances, it led to significant reductions in the availability of diagnostic imaging technologies, obstetric and primary care services, and outpatient care. 34 Many "nonprofit" health systems rake in enormous profits. In 2018, Kaiser Foundation Health Plan and Hospitals had an operating surplus of $1.9 billion.…”
Section: Corporate Medicinementioning
confidence: 99%
“…Claire O'Hanlon and coauthors compare the attributes of the 306 rural hospitals that created health system affiliations in 2009 and 17 with those of rural hospitals that did not. They found that operating margins increased significantly following rural hospital affiliation with a health system [26]. However, affiliating hospitals "experienced a significant reduction in on-site diagnostic imaging technologies, the availability of obstetric and primary care services, and outpatient nonemergency visits."…”
Section: Health Care and Accessmentioning
confidence: 99%